Answer:
0.3413
Step-by-step explanation: Hope this helps :)
Answer:
Correct answer is B
Step-by-step explanation:
hope it helps ^^
Answer:
See explanation
Step-by-step explanation:
Assuming the given inequality is ![2x+3y\le12](https://tex.z-dn.net/?f=2x%2B3y%5Cle12)
Then the corresponding linear equation is ![2x+3y=12](https://tex.z-dn.net/?f=2x%2B3y%3D12)
When x=0, we have ![2*0+3y=12](https://tex.z-dn.net/?f=2%2A0%2B3y%3D12)
![\implies 3y=12\implies y=4](https://tex.z-dn.net/?f=%5Cimplies%203y%3D12%5Cimplies%20y%3D4)
When y=0, we have ![2x+3*0=12](https://tex.z-dn.net/?f=2x%2B3%2A0%3D12)
![\implies 2x=12\implies x=6](https://tex.z-dn.net/?f=%5Cimplies%202x%3D12%5Cimplies%20x%3D6)
The T-table is:
<u>x | y</u>
0 | 4
6 | 12
We plot this points and draw a solid straight line as shown in the attachment.
Now let us test the origin: (0,0) by plugging x=0 and y=0 into the inequality.
![2*0+3*0\le12](https://tex.z-dn.net/?f=2%2A0%2B3%2A0%5Cle12)
....This is true so we shade the lower half plane as shown in the attachment.
this picture has bad quality, please resend with better picture so i can answer all of them
B. Is the answer to your question